2022
DOI: 10.1126/sciadv.add2032
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights for neutralization of Omicron variants BA.1, BA.2, BA.4, and BA.5 by a broadly neutralizing SARS-CoV-2 antibody

Abstract: In this study, by characterizing several human monoclonal antibodies (mAbs) isolated from single B cells of the COVID-19–recovered individuals in India who experienced ancestral Wuhan strain (WA.1) of SARS-CoV-2 during early stages of the pandemic, we found a receptor binding domain (RBD)–specific mAb 002-S21F2 that has rare gene usage and potently neutralized live viral isolates of SARS-CoV-2 variants including Alpha, Beta, Gamma, Delta, and Omicron sublineages (BA.1, BA.2, BA.2.12.1, BA.4, and BA.5) with IC … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 61 publications
4
60
0
Order By: Relevance
“…Next, we revealed that all three mAbs strongly bind spike protein with Kd values in low nM to pM range, by both BLI (Figure S2) and Mesoscale binding assay (Mesoscale Discovery) (Figure 2A). Additionally, in agreement with binding data they all potently neutralize the ancestral WA.1 live virus in a focus-reduction neutralization mNeonGreen (FRNT-mNG) assay (Figure 2B and 2C) (14,15). Taken together, these results confirm high binding affinity and potent neutralizing capacity of all three shared mAbs against the SARS-CoV-2 WA.1 strain.…”
Section: Identification and Characterization Of Shared Human Mabs To ...supporting
confidence: 85%
See 4 more Smart Citations
“…Next, we revealed that all three mAbs strongly bind spike protein with Kd values in low nM to pM range, by both BLI (Figure S2) and Mesoscale binding assay (Mesoscale Discovery) (Figure 2A). Additionally, in agreement with binding data they all potently neutralize the ancestral WA.1 live virus in a focus-reduction neutralization mNeonGreen (FRNT-mNG) assay (Figure 2B and 2C) (14,15). Taken together, these results confirm high binding affinity and potent neutralizing capacity of all three shared mAbs against the SARS-CoV-2 WA.1 strain.…”
Section: Identification and Characterization Of Shared Human Mabs To ...supporting
confidence: 85%
“…Here, we focused on three mAbs that potently neutralize the ancestral WA.1 strain, but differentially neutralize SARS-CoV-2 variants for further characterization. The immunogenetic analysis confirms that all three mAbs were encoded by IGHV3-53/66 and IGHV3-30 genes and were publicly shared (14). While the Cryo-EM structure of all three mAbs showed bivalent spike binding, two mAbs (002-02 and 034-32) targeted the class-1 RBD epitope whereas mAb 002-13 targeted a relatively conserved class-4 epitope.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations